Divergent outcomes of gut microbiota alteration upon use of spectrum antibiotics in high sugar diet-induced diabetes in rats. Issue 46 (20th July 2018) - Prajapati, Bhumika; Jena, Prasant Kumar; Patel, Sweta; Seshadri, Sriram
Abstract : A sugar rich diet induces inflammation and insulin resistance (IR) mainly through gut microbiota alteration. Abstract : Background : A sugar rich diet induces inflammation and insulin resistance (IR) mainly through gut microbiota alteration. Gut dysbiosis increases lipopolysaccharide (LPS) and reduces propionate and butyrate levels to impair the insulin signalling cascades by different molecular pathways, which progresses into IR. The present study was designed to investigate the effect of spectrum specific antibiotics on the modulation of gut microbiota and its signalling pathways to prevent diet-induced diabetes. Methods : Healthy male Wistar rats were divided into a non-diabetic group with a control diet (CD), a diabetic group with a high sucrose diet (HSD) and two antibiotic fed groups (linezolid and cefdinir; administered by oral gavage) along HSD. Physiological, biochemical, inflammatory and microbiome parameters were examined. Results : Cefdinir administration in HSD rats reduced fasting glucose, serum triglyceride, and cholesterol levels compared to HSD alone. In addition, cefdinir reduced serum LPS by decreasing the population of Gram-negative phyla, that is, Bacteroidetes and Proteobacteria in the fecal content. Furthermore, cefdinir treatment decreased hepatic/ileal/colonic Tlr4, Nlr1, and Nf-κB at the mRNA level. Moreover, cefdinir-treated rats had shown increased fecal butyrate and propionate and reduced acetate levels compared to HSD alone. Cefdinir treatment also induced ileal/colonic Gpr43 and Glut4 at the mRNA level after 12 weeks of administration. Conclusions : Taken together, these data suggest that administration of a Gram-negative spectrum antibiotic, that is, cefdinir, has modulated the gut microbiota, and reduced serum LPS and triglycerides, which prevented the progression of IR and inflammation in HSD rats.